Comparasion of the Grade of Day Old Chick Broiler Chickens in Different Cages to Mortality and Feed Conversion Ratio - Ikhsan, Raihan Fairuz; Tugiyanti, Elly (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
This research aims to find out and study the influence of differences in initial weight of broiler chickens on mortality and feed conversion ratio. The internship will be held for 1 period starting from 30 September – 22 December 2023 in Arresie Village, Paleteang District, Pinrang, South Sulawesi. The variables observed were mortality and FCR. The material used was broiler chickens with the platinum grade Lohmann strain in cage 1 with a population of 7,500, the second cage used silver grade Lohmann strain broiler chickens with a population of 7,500. The method used is the observation method. The variables measured were mortality and FCR in two different cages with the same population size. The analysis method used is the independent T-Test. The research results showed that the difference in doc weight on mortality and feed conversion ratio (FCR) had no significant differences (p>0.05). The difference in doc weight on mortality and feed conversion ratio (FCR) in different cages was not significantly different (P>0.05).